Application of a radio link system in the 400MHz band for remote supervision and control of SEDAPAL service stations in Peru (LACCEI, 2024)
Within the program for the improvement and modernization of drinking water and sewerage service stations in Latin America, there are projects to expand and improve the service due to its projection of population growth and modernization of the service, since in most cases there is a lack of updating of automation designs which hinders the supply of drinking water. In addition, in some cases in Latin American cities, the monitoring and control of the stations (reservoirs, wells, inlet chambers, re-pumping chambers, etc.) has been carried out manually. For this reason, in this investigation, the interconnection of the SEDAPAL stations is considered, which will be carried out wirelessly, interconnecting the stations through radio links, through a study of different factors such as geographical profiles, height of the antennas, calculation of fresnel zones, antenna gain, azimuth calculation, transmission power, effective radiated power, losses generated by free space, among others.